EM PASSO DE TANGO NO CALOR CARIOCA: ERRÂNCIA E DESPERTENCIMENTO EM TODOS OS PECADOS DO MUNDO, DE NORBERTO PRESTA (Muitas Vozes, 2024)
Inserted in the debate on the manifestations of the “Thought of outside” in the context of contemporary Latin American literature, I propose a reading of the wandering movements of the character Manuel, of Argentine origin, through Rio de Janeiro in Todos os pecados do mundo: a carioca novel. I take, as principles, the concept of “foreigner”, by Néstor Canclini (2016) and Julia Kristeva (1994) to analyze the deterritorialized identity of the protagonist of the plot. Manuel's strangeness, understood basically through his way of walking and his peculiar attempts to root himself in the city, allows to conclude that he inhabits an in-between place between cultures that conforms the symbolic representation of the lack of belonging. I also allude to the nature of the outside present in the constitutive transit of the novel, as a fiction, with autofictional or alterfictional forms, as proposed by Evandro Nascimento (2017), and between the status of fiction and the testimony of the world, according to the understanding of Julián Fuks (2017).